2020
DOI: 10.1002/chem.202003758
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Divergent Oxidative Cyclization from Strictosidine and Vincoside Derivatives: Second‐Generation Total Synthesis of (−)‐Cymoside and Access to an Original Hexacyclic‐Fused Furo[3,2‐b]indoline

Abstract: The second‐generation synthesis of (−)‐cymoside as well as the formation of a new hexacyclic‐fused furo[3,2‐b]indoline framework is reported. After a Pictet–Spengler condensation between secologanin tetraacetate and tryptamine, the course of the cyclization of the 7‐hydroxyindolenine intermediate, generated by oxidation with an oxaziridine, depended on the stereochemistry of the 3‐position. The 3‐(S)‐strictosidine stereochemistry delivered efficiently the scaffold of cymoside via intramolecular coupling with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…The Pictet–Spengler reaction, discovered in 1911 by Amé Pickett and Theodore Spengler, is originally a cyclization of a phenethylamine 1 and a formaldehyde dimethyl acetal 2 to produce 1,2,3,4-tetrahydroisoquinoline 3 in the presence of hydrochloric acid ( Scheme 1 ). 1 After that, a variety of modified reaction systems for the Pictet–Spengler reaction have been developed for the construction of valuable heterocyclic scaffolds, 2 such as Brønsted acids, 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 Lewis acids, 39 40 41 transition metal catalysts, 42 43 44 45 46 organocatalysts, 26 27 47 48 and enzyme strictosidine synthases. 13 49 Meanwhile, the use of suitably substituted amine derivatives such as β-arylethylamines, tryptamines, or functionalized aromatic amines with an aldehyde or ketone is essential for the progress of the Pictet–Spengler reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The Pictet–Spengler reaction, discovered in 1911 by Amé Pickett and Theodore Spengler, is originally a cyclization of a phenethylamine 1 and a formaldehyde dimethyl acetal 2 to produce 1,2,3,4-tetrahydroisoquinoline 3 in the presence of hydrochloric acid ( Scheme 1 ). 1 After that, a variety of modified reaction systems for the Pictet–Spengler reaction have been developed for the construction of valuable heterocyclic scaffolds, 2 such as Brønsted acids, 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 Lewis acids, 39 40 41 transition metal catalysts, 42 43 44 45 46 organocatalysts, 26 27 47 48 and enzyme strictosidine synthases. 13 49 Meanwhile, the use of suitably substituted amine derivatives such as β-arylethylamines, tryptamines, or functionalized aromatic amines with an aldehyde or ketone is essential for the progress of the Pictet–Spengler reaction.…”
Section: Introductionmentioning
confidence: 99%
“…An active area of research is the development of new strategies to access complex MIAs, such as vinblastine ( 3 ), through a combination of isolation from natural sources, biosynthesis, and total synthesis. , We identified the natural product (−)-strictosidine ( 4 ) as an attractive entryway to access MIAs and derivatives . (−)-Strictosidine ( 4 ) is the last common biosynthetic precursor to all MIAs.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, we demonstrated that "strictosidyne" (22) and "strictosamidyne" (23) could be generated from precursors 19 and 20, respectively, by performing Diels−Alder trapping experiments (Scheme 7). Each silyltriflate was independently subjected to furan (21) and cesium fluoride in acetonitrile at 50 °C.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, we turned to using imine 16 for the asymmetric Michael addition, which contained a phenylthiol group serving as the precursor of the terminal olefin. Sulfinamide 16 was prepared in 93% yield through condensation of 4-(phenylthiol)butanal (15) 11 and the chiral auxiliary (R)-tert-butanesulfinamide (12) With chiral building block 19 in hand, the stage was set for constructing the piperidine E ring via a Mitsunobu reaction (Scheme 3). As a consequence, the treatment of 19 with PPh 3 and diisopropyl azodicarboxylate (DIAD) in toluene promoted the smooth cyclization of the E ring and afforded compound 20 in 80% yield.…”
mentioning
confidence: 99%
“…Therefore, we turned to using imine 16 for the asymmetric Michael addition, which contained a phenylthiol group serving as the precursor of the terminal olefin. Sulfinamide 16 was prepared in 93% yield through condensation of 4-(phenylthiol)­butanal ( 15 ) and the chiral auxiliary ( R )- tert -butanesulfinamide ( 12 ). Next, coupling of fragments 16 and 9 was achieved by treatment with a strong base (LiHMDS) in THF, furnishing the desired Michael adduct 17 as the major diastereomer with C4 and C5 configurations secured.…”
mentioning
confidence: 99%